La città del sole : dialogo poetico = The City of the Sun : a poetical dialogue - Campanella, Tommaso, 1568-1639 (Biblioteca italiana., 1981)
Drummond -- Who I am -- Bummer summer -- After the baby -- Neighbors -- Drum and Dorene -- Meeting Dorene -- Race -- Tall tale -- New boy -- Drum, Dorene and Louis -- Someone -- Party -- Tall tale, too -- Going to get Rae -- Drum, Dorene, Louis and Rae -- Rae -- Promise -- Playground -- Friendly four -- Rain -- Fuss -- Punished -- When summer ends -- Let's make a town -- Here comes the truck -- We did it! -- In the town of Goodsummer -- Parade -- At the movies -- At the bank -- At school -- At the office building -- At the library -- At the pet shop -- At the concert hall -- Goodbyes -- Goodbye, Rae -- E-mail -- Goodbye to Goodsummer.